Pengaruh Profitabilitas terhadap Harga Saham - Arsyandra, Muhammad Putu; Rieswandha Dio Primasatya (Politeknik Ganesha Medan, 2024)
The capital market plays a crucial role in supporting economic growth, enabling the trading of stocks and bonds. Investment in the capital market involves technical and fundamental analysis, with financial reports significantly influencing stock prices and investor returns. Macroeconomic factors and company performance also impact stock movements. Fundamental financial ratios play a central role in determining stock values. The aim of this research is to examine the effects of fundamental financial ratios such as GPM, PMR, ROA, ROE, and ROS on stock prices. The sampling method used is purposive sampling. In the analysis, this study applies multiple linear regression, including measures of determination coefficients, F-tests, and t-tests. Before hypothesis testing, initial steps involve descriptive statistical analysis and testing classical assumptions to ensure that data is free from assumptions such as normality, multicollinearity, heteroskedasticity, and autocorrelation. The population studied consists of industrial and manufacturing companies in Indonesia, with the sample comprising manufacturing companies in the mining sub-sector listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2021. The research findings conclude that ROA has a significant negative impact on stock prices, while ROE has a positive but insignificant impact. GPM also has a positive but insignificant impact on stock prices, as does NPM. On the other hand, ROS has a significant negative impact on stock prices. For future research, other factors that may influence stock prices and their impact on the variables under study can be considered